INTEGRATION OF ISLAMIC SPIRITUAL EMOTIONAL AND INTELLECTUAL EDUCATION IN VOCATIONAL HIGH SCHOOLS - Aisyah Kurniawati; Sutarno Sutarno; Sariman Sariman (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2022)
The results of education are not only cognitively centered but are emphasized on everyday moral behavior, which reflects on spiritual intellectual intelligence. This study aims to describe and analyze the planning and implementation of the integration of Islamic spiritual emotional and intellectual education in vocational high schools. The results of this study: Integration of Spiritual, Emotional, and Intellectual Education Curriculum at Nahdlatul Ulama Al Barokah Babat Vocational High School begins with curriculum integration planning in five stages, namely concept formulation, curriculum formulation at the education unit level by adding Arabic and NU subjects, preparation of academic and non-academic programs. The process of implementing curriculum integration through intra-curricular activities containing Arabic and Nuanism subjects, religious extracurricular activities, and habituation activities. The education curriculum integration model is a multidisciplinary model and a transdisciplinary model.